The Differences of 10% Neutral Buffered Formalin, 4% Paraformaldehyde, and Bouin Solution in Newborn Rat Brain - A.A.Ayu Asri Prima Dewi; Fransiscus Fiano Anthony Kerans; Dewa Ayu Agung Alit Suka Astini; Luh Gde Evayanti; Ni Putu Diah Witari; Komang Trisna Sumadewi (Warmadewa University, 2024)
Rats are widely used in the study of embryological development of the central nervous system and its congenital disorders. Therefore, tissue fixation is very important in obtaining a good picture of the central nervous system, especially in newborn rats. This study aims to determine the difference in fixation using a solution of 10% neutral buffered formalin, 4% paraformaldehyde, and Bouin solution in the brain tissue of newborn rats. This experimental study used a post-test only controlled-group design with 18 newborn rats aged zero day. After randomization, the pups were grouped into 3 treatment groups, namely: fixation with 10% neutral buffered formalin solution (P1, n = 6), and fixation with 4% paraformaldehyde solution (P2, n = 6), and fixation with Bouin solution (P3, n = 6). Assessment using Hematoxylin Eosin staining, and analyzed by blinding based on the histology of the cerebral tissue (cell nucleus staining, cytoplasmic staining, staining clarity, uniformity of staining). Five cerebrum fields were examined. Data analysis used Kruskall Wallis test and post hoc Mann Whitney test using SPSS. The result was a significant difference in the histology of the brain tissue of newborn rats with the fixation of a solution of 10% neutral buffered formalin, 4% paraformaldehyde and Bouin solution (p = 0.001). Brain tissue fixation using 10% neutral buffered formalin solution showed better quality of histological pictures compared to 4% solution of paraformaldehyde solution and Bouin solution (p <0.05).